2014
DOI: 10.1089/end.2013.0766
|View full text |Cite
|
Sign up to set email alerts
|

Same-Session Bilateral Retrograde Intrarenal Surgery for Upper Urinary System Stones: Safety and Efficacy

Abstract: Bilateral same-session RIRS is a safe and effective procedure that can be considered a first-line treatment for bilateral UUSS in select patients. The SFR is satisfactory, especially in patients with a stone burden <25 mm. At minimum a unilateral Double-J stent should be placed in patients undergoing bilateral RIRS to avoid postrenal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
3
18
0
2
Order By: Relevance
“…According to our results, the stone-free rate of this surgery was 81.2% and between 70% and 97% in the international literature. [4][5][6][7][11][12][13][14] These studies mentioned above showed that our results were consistent with the international literature. Up to date, no specific classification system has been described for per-operative complication of RIRS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our results, the stone-free rate of this surgery was 81.2% and between 70% and 97% in the international literature. [4][5][6][7][11][12][13][14] These studies mentioned above showed that our results were consistent with the international literature. Up to date, no specific classification system has been described for per-operative complication of RIRS.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7][8] A recent study reported modified Satava Classification System (SCS) that categorizes the complications of RIRS. 6 The authors stated that the modified SCS can facilitate patients to understand the safety of RIRS.…”
Section: Introductionmentioning
confidence: 99%
“…Alkan et al [55] treated simultaneously 201 bilateral stones in 44 patients, and found an overall SFR of 88.6%. When the patients grouped according to stone burden, SFR was 100% and 80% for stones smaller and larger than 25 mm, respectively.…”
Section: Rirs For Simultaneous Bilateral Stonesmentioning
confidence: 99%
“…Ayrıca tek seansta taşsızlık sağlanabilmesi ek girişim ve operasyon ihtiyacını da ortadan kaldıracaktır (12,13).…”
Section: Eş Zamanlı Böbrek Ve üReter Taşıunclassified